2007
DOI: 10.1093/toxsci/kfm130
|View full text |Cite
|
Sign up to set email alerts
|

Uranium Induces Apoptosis and Is Genotoxic to Normal Rat Kidney (NRK-52E) Proximal Cells

Abstract: Uranium (U) is a heavy metal used in the nuclear industry and for military applications. U compounds are toxic. Their toxicity is mediated either by their radioactivity or their chemical properties. Mammalian kidneys and bones are the main organs affected by U toxicity. Although the most characteristic response to U exposure is renal dysfunction, little information is available on the mechanisms of its toxicity at the molecular level. This report studied the genotoxicity of U. Apoptosis induction in normal rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(68 citation statements)
references
References 27 publications
4
52
0
1
Order By: Relevance
“…Chez le rat, après exposition chronique (3 mois, 40 mg/kg) l'uranium induit une augmentation de marqueurs du stress oxydant (peroxydation lipidique et oxydation du glutathion (GSSG)) au niveau rénal (Linares et al, 2006). In vitro, sur des cellules rénales en culture, une augmentation de la production d'espèces réactives de l'oxygène est également observée et impliquerait une entrée des cellules en apoptose à partir de concentrations élevées (>600 µM) (Thiebault et al, 2007). Comme cela a été observé pour d'autres métaux, les perturbations de l'homéostasie redox sont donc susceptibles d'entraîner des phénomènes d'adaptation allant d'une induction de la réponse antioxydante à une mort cellulaire programmée (apoptose) afin de préserver le tissu environnant.…”
Section: Stress Oxydantunclassified
“…Chez le rat, après exposition chronique (3 mois, 40 mg/kg) l'uranium induit une augmentation de marqueurs du stress oxydant (peroxydation lipidique et oxydation du glutathion (GSSG)) au niveau rénal (Linares et al, 2006). In vitro, sur des cellules rénales en culture, une augmentation de la production d'espèces réactives de l'oxygène est également observée et impliquerait une entrée des cellules en apoptose à partir de concentrations élevées (>600 µM) (Thiebault et al, 2007). Comme cela a été observé pour d'autres métaux, les perturbations de l'homéostasie redox sont donc susceptibles d'entraîner des phénomènes d'adaptation allant d'une induction de la réponse antioxydante à une mort cellulaire programmée (apoptose) afin de préserver le tissu environnant.…”
Section: Stress Oxydantunclassified
“…With high concentrations of DU, the cells underwent necrosis (Thiébault et al 2007). The MI of the populations of Monte Alegre, Prainha, and Alenquer did not present significant differences compared to the control population (P>0.05).…”
Section: Discussionmentioning
confidence: 75%
“…Thiébault et al (2007), using the comet assay, detected double-and single-strand breaks and/or labile sites on the DNA, after exposure of NRK-52 E cells to sublethal and lethal concentrations of DU. DNA lesions increased in direct proportion to the uranium concentration.…”
Section: Discussionmentioning
confidence: 99%
“…That is, low concentrations of uranium induced small amount of DNA damage and cellular modifications, which can be efficiently repaired through adaptation responses, although some of these DNA damage might be misrepaired leading to apoptotic cell death (Thiebault et al, 2007). At higher concentrations, uranium induced strong cellular modifications and DNA damage producing apoptotic cell death (Thiebault et al, 2007). Previously we showed that satratoxin H induced ROS generation and the following phosphorylation of p38 MAPK (Nusuetrong et al, 2005(Nusuetrong et al, , 2008.…”
Section: Discussionmentioning
confidence: 98%
“…Our results are in accordance with a previous study about uranium. That is, low concentrations of uranium induced small amount of DNA damage and cellular modifications, which can be efficiently repaired through adaptation responses, although some of these DNA damage might be misrepaired leading to apoptotic cell death (Thiebault et al, 2007). At higher concentrations, uranium induced strong cellular modifications and DNA damage producing apoptotic cell death (Thiebault et al, 2007).…”
Section: Discussionmentioning
confidence: 99%